THE INFLUENCE OF INFORMATION TECHNOLOGY AND INTEGRATED MANAGEMENT INFORMATION SYSTEMS ON EMPLOYEE PERFORMANCE IN RSUD Dr. CHASBULLAH ABDULMADJID, BEKASI CITY - Riris Lestiowati, Riris; Taufik , Ahmad; M.Suwandi, M.Suwandi; Rukiastiandari, Sinta (Journal of Industrial Engineering & Management Research, 2021)
: This study aims to determine the effect of management technology and information systems on employee performance at dr. Masbullah Abdulmajid Hospital, Bekasi City. The method used in this study is a survey approach, this type of research is associative and the research used is explanatory ( explanatory research). The sampling technique used is a random sampling of 100 respondents. The data analysis method used is multiple linear regression, t test, F test, and cyclical assay. From the results of the study, there is a positive and significant influence between technology and management information systems on employee performance at dr. Masbullah Abdulmajid Hospital, Bekasi City t count 6,865> t table (1,661). Second, there is a positive and significant influence between technology and information management systems on employee performance at dr. Kasbullah Abdulmajid Hospital, Bekasi City where t count is 4,257> t table (1,661). Third, there is a positive and significant influence between technology and information management systems on the performance of employees at RSUD Dr. Chaasbullah Abdulmajid Bekasi City (48.325)> F table of 2.359. Together, technology and information systems manage the performance of employees at RSUD Dr. Chaasbullah Abdulmajid Bekasi City with a determination coefficient of 50.4%. And from the results of R2 (coefficient of determination) states that the variable technology and information systems management the performance of employees at RSUD Dr. Chaasbullah Abdulmajid Bekasi City which is 50.40%, while the remaining 49.60% is influenced by other factors not examined in this study